Pengaruh Model TSTS Berbasis Media Qna Puzzle Terhadap Hasil Belajar Siswa Tema 3 Subtema 2 Kelas III SDN Petompon 02 Semarang - Refine Dezan Aryono Dewi (Jurnal Inovasi Pembelajaran di Sekolah, 2021)
This research purposed to know the model influence of Two Stay Two Stray (TSTS) based on media Puzzle QnA on material of Tema 3 Sub tema 2 for third grade students of Primary School. The experiment quasi research with subject third grade students as a experiment class which was given learning of Two Stay Two Stray (TSTS) based on media Puzzle QnA and third B grade as a control group was given konventional learning with media Puzzle QnA. The learning result data got through pretest and post test and was analysed used U Mann Whitney test. The result research showed that model of Two Stay Two Stray (TSTS) based on Puzzle QnA has positive influence to tematik learning result of tema 3 subtema 2 to third grade students of SDN Petompon 02. This case proved from the test result of U Mann Whitney with significant score 0,037, with averages the study result on this learning reached 84,03 significantly more better than direct learning has average 78,33. This difference happened because there is the meaningfull learning process, more activated students in study process, has responsible to convey discussion result or looked for discussion result from other group and reconvey to their groups. The happiness learning encouraged students to be active to study so has impact to get the study result more better than direct learning.